2014
DOI: 10.1111/nph.12843
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid nuclear signaling recruits HSP90 activity

Abstract: SummaryHeat shock protein 90 (HSP90) controls a number of developmental circuits, and serves a sophisticated and highly regulatory function in signaling pathways. Brassinosteroids (BRs) control many aspects of plant development.Genetic, physiological, cytological, gene expression, live cell imaging, and pharmacological approaches provide conclusive evidence for HSP90 involvement in Arabidopsis thaliana BR signaling.Nuclear-localized HSP90s translocate to cytoplasm when their activity is blocked by the HSP90 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 67 publications
1
64
0
Order By: Relevance
“…protect BES1 against BIN2 kinase, recruiting PP2A to dephosphorylate it, or both. However, HSP90 is also necessary for nuclear retention and activity control of BIN2 kinase (Samakovli et al, 2014). Therefore, the role of HSP90 in controlling BES1 phosphorylation state might be more complicated we might assume.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…protect BES1 against BIN2 kinase, recruiting PP2A to dephosphorylate it, or both. However, HSP90 is also necessary for nuclear retention and activity control of BIN2 kinase (Samakovli et al, 2014). Therefore, the role of HSP90 in controlling BES1 phosphorylation state might be more complicated we might assume.…”
Section: Discussionmentioning
confidence: 97%
“…They regulate BR responsive genes such as CPD and DWF4 (Samakovli et al, 2014;Shigeta et al, 2014). To date, it has remained indeterminate which portions of BES1 protein are responsible for the binding to HSP90.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis , HSP90, as a molecular chaperone, contributes to BR-mediated gene expression through complex formation with two major TFs, BZR1 and BES1 (Samakovli et al, 2014; Shigeta et al, 2015). A recent study reported that HSP90 is pivotal in the transition from vegetative to reproductive phase in Arabidopsis and that depletion of HSP90 mRNA levels causes extreme variation in the expression of flowering genes, and disturbs flower determination and patterning (Margaritopoulou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibitor of HSP90 ATPase activity-geldanamycin-suppressed BR-induced downregulation of key biosynthesis genes-CONSTITUTIVE PHOTHOMOR-PHOGENESIS AND DWARFISM (CPD) and DWARF4 in vivo (Shigeta et al 2014). HSP90 also assists nuclear localization of BRs signaling component-BIN2 (BRAS-SINOSTEROID INSENSITIVE 2) protein and geldanamycin treatment force BIN2 translocation to cytosol (Samakovli et al 2014). These point at involvement of HSPs into brassinosteroid signaling and regulation of BR-dependent genes.…”
Section: Introductionmentioning
confidence: 96%